Analisis Cakupan Penemuan Kasus Tuberkulosis (Treatment Coverage) Berdasarkan Faktor Demografis dan Komorbiditas di Puskesmas Ciracas Tahun 2023-2024 - Hardiyanti, Anggie; Helda, Helda; M. Irzal, Mufti As Siddiq; Monica, Mareska (UI Scholars Hub, 2025)
Tuberculosis (TB) remains a major global and national health burden, with case detection coverage still below target in several regions. The success of TB control programs largely depends on achieving adequate treatment coverage. In East Jakarta, Ciracas Primary Health Center recorded a treatment coverage of 75% (497 cases) in 2023, the lowest among ten centers, and an increase to 84% (509 cases) in 2024, though still below the national target of 90%. To analyze TB case detection coverage based on demographic factors and comorbidities (diabetes mellitus and Human Immunodeficiency Virus) at Ciracas Primary Health Center during 2023–2024. This study employed a cross-sectional design using secondary data from the Ciracas Tuberculosis Information System (SITB). All people with TB with complete records were included through total sampling. Data were analyzed using univariate, bivariate, and multivariate analysis with Stata/IC15.1, to assess the association between demographic and comorbidity factors and case detection coverage. A total of 1,006 TB cases were recorded, with most patients in the productive age group (18–59 years; 70.6%) and male (61.6%). Diabetes mellitus comorbidity was found in 13.8% of cases, and HIV-positive status in 2.2%. Productive age was significantly associated with TB occurrence, both in patients with diabetes (OR: 0.223; 95% CI: 0.158–0.311) and without diabetes (OR: 0.19; 95% CI: 0.161–0.22), while sex and HIV status were not significant. Productive-age individuals and those with diabetes mellitus are the most at-risk populations for TB in Ciracas. Enhanced Active Case Finding (ACF) among high-risk groups is required to accelerate progress toward the national TB elimination target. Keywords: Tuberculosis; treatment coverage;demography; diabetes mellitus; HIV